2014
DOI: 10.3109/21678421.2014.881376
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival with an ambulatory model of non-invasive ventilation implementation in motor neuron disease

Abstract: Non-invasive ventilation (NIV) increases survival and quality of life in motor neuron disease (MND). NIV implementation historically occurred during a multi-day inpatient admission at this institution; however, increased demand led to prolonged waiting times. The aim of this study was to evaluate the introduction of an ambulatory model of NIV implementation. A prospective cohort study was performed. Inclusion criteria were referral for NIV implementation six months pre- or post-commencement of the Day Admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…We speculate that the benefits of NIV we observed in bulbar disease may, in part, reflect earlier initiation 21. Our study showed that across the phenotypes, median time to NIV initiation (from disease onset) was shortest in patients with ALS-bulbar.…”
Section: Discussionmentioning
confidence: 59%
“…We speculate that the benefits of NIV we observed in bulbar disease may, in part, reflect earlier initiation 21. Our study showed that across the phenotypes, median time to NIV initiation (from disease onset) was shortest in patients with ALS-bulbar.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, there is increasing evidence for successful outpatient management in non-COPD patients requiring long-term NIV [20-24]. However, most of these patients receive long-term NIV due to neuromuscular and chest wall diseases and therefore the results are not comparable to COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…NIV can be initiated in any setting experienced in NIV. No site of NIV initiation has been demonstrated to be superior to another, with home, ambulatory care and even telemonitoring all reporting successful establishment of NIV. The current trend, especially in view of the major motor disability of these patients, is to avoid hospitalization and all outpatient approaches are highly appreciated by patients and are associated with health cost savings .…”
Section: How Should Als Patients Be Ventilated?mentioning
confidence: 99%
“…The current trend, especially in view of the major motor disability of these patients, is to avoid hospitalization and all outpatient approaches are highly appreciated by patients and are associated with health cost savings . Sheers et al showed that outpatient initiation of NIV can save time and consequently improve patient survival …”
Section: How Should Als Patients Be Ventilated?mentioning
confidence: 99%